Migration response to an immigration shock: Evidence from Russia's aggression against Ukraine - David Zuchowski (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Russia's attacks against Ukraine have triggered massive and unexpected migration movements. In this paper, I examine the impact of the inflow of Ukrainians that resulted from Russia's aggression in 2014 on local migration patterns in Poland. For identification, I use an instrumental variable approach drawing on unique historical data on the forced resettlement of Ukrainians in Poland after World War II. The results show that the regional inflow of immigrants decreases both internal and international out-migration of the Polish population. I provide supportive evidence that the decrease in out-migration is due to the upscaling of local labor markets. – – Die Angriffe von Russland auf die Ukraine haben massive und unerwartete Migrationsbewegungen ausgelöst. In diesem Artikel untersuche ich die Auswirkungen des Zustroms ukrainischer Arbeitskräfte infolge der russischen Aggression im Jahr 2014 auf lokale Migrationsbewegungen in Polen. Zur Identifizierung der Effekte verwende ich einen Instrumentalvariablenansatz, der sich auf einzigartige historische Daten zur Zwangsumsiedlung ukrainischer Familien in Polen nach dem Zweiten Weltkrieg stützt. Die Ergebnisse zeigen, dass die regionale Zuwanderung sowohl die interne als auch die internationale Abwanderung der polnischen Bevölkerung verringert. Ich finde Indizien dafür, dass dieser Rückgang der Abwanderung auf das Hochskalieren der lokalen Arbeitsmärkte zurückzuführen ist.
Keywords: F22; J61; O15; 330; Migration; immigrant workers; Poland; Ukraine